Juventude e desenvolvimento regional: um estudo sobre a inserção das coletividades geracionais jovens no processo de desenvolvimento da microrregião de Toledo, PR - Oliveira, Luciana Vargas Netto (2013)
The Toledo geographic micro region, consisting of twenty-one municipalities, holds a significant economic, political and social position in the western region, as well in the State of Paraná, Brazil, and is considered to be developed based on the various positive indicators it displays. However, we notice that young people, as a distinct segment of the population, have not necessarily been able to include themselves in this process. Thus, the object of this research is focused on the relationship between the different ways to integrate youth between 18 and 29 years of age in the process of regional development and the possibilities of social change. The main hypothesis is that there seems to be an unequal insertion of different generational youth communities in the development of this region, depending on their socioeconomic status, their ethnic and racial characteristics and the gender relations between them. Therefore, the study sought to give an overview of the region s young population, who is considered to be an actor in the regional development process based on the endogenous growth theories and examine how the inclusion of these different youths are outlined in the region s economic, social and professional spheres. The methodology of the research was based on the combined quantitative and qualitative approach, considering them complementary. The technique of data gathering was carried out at an international, national, state and municipal level on sources of secondary data, provided by different government agencies, research institutes, non-governmental organizations, among others. The indicators used refer to education, professional training, employment and income. The results showed that approximately thirty-three percent of young people between 18 and 29 years of age living in the micro region of Toledo can be classified as not included in the development process; around thirty-six percent of young people can be categorized as integrated subordinately or precariously; a third classification refers to an average level of integration, which include twenty-nine percent of young people surveyed; and in regard to a dominant integration form, only a little over two percent are portrayed. The analysis of the integration of young people considering their ethnic and racial characteristics showed that inequalities are even more intense, with clear disadvantages for young people self-identified as "blacks" and "browns" compared to young people self-identified as "white". The results on gender differences indicate that although young women have higher levels of education, they represent the majority among those excluded from the labor market and, consequently, from the assessment of personal income. On the other hand, the male youths, whose education levels are proportionally lower, appear in greater numbers in the labor market and represent the majority in every analyzed income group. Ergo, these different and unequal ways of integrating the young generational collectivities in the Toledo micro region appear to function as a reinforcement mechanism to the established hierarchies, which hinder and inhibit the potential development of social change in the region.